User Experience Transformation in Enterprise Communication Platforms: A Longitudinal Analysis of Google Chat’s UI Refresh Initiative - Hemanth Aditya (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This article examines the impact of user experience (UX) improvements in corporate communication tools, specifically analyzing the recent UI refresh of Google Chat as a representative case study. The article explores how interface redesign influences workplace productivity and team collaboration in remote work settings through a mixed-methods investigation combining user behavior analysis, performance metrics, and satisfaction surveys. The findings indicate that optimized navigation patterns, restructured home screen layouts, and enhanced task management features significantly improve information discovery and cross-functional communication efficiency. The article reveals that thoughtful UX improvements can substantially reduce cognitive load, streamline workflow processes, and enhance team coordination in distributed work environments. Furthermore, the article identifies key design principles that drive user adoption and engagement in enterprise communication platforms. These insights contribute to the growing knowledge on digital workplace transformation and provide practical implications for organizations investing in communication tool improvements. The article concludes by proposing a framework for evaluating and implementing UX enhancements in enterprise communication systems while acknowledging the dynamic nature of remote work requirements and user expectations.